2011
DOI: 10.1016/j.lfs.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin (PHB) acts as a potent survival factor against ceramide induced apoptosis in rat granulosa cells

Abstract: Aim Ceramide is a key factor in inducing germ cell apoptosis by translocating from cumulus cells into the adjacent oocyte and lipid rafts through gap junctions. Therefore studies designed to elucidate the mechanistic pathways in ceramide induced granulosa cell (GC) apoptosis and follicular atresia may potentially lead to the development of novel lipid-based therapeutic strategies that will prevent infertility and premature menopause associated with chemo and/or radiation therapy in female cancer patients. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…Our studies have shown that infection of undifferentiated GC from preantral follicles with a PHB adenoviral construct resulted in over-expression of PHB that markedly attenuated ceramide-, staurosporine-, campothecine- and serum withdrawl-induced apoptosis via the intrinsic apoptotic pathway (Chowdhury et al, 2007, 2011, 2013, 2014; Wang et al, 2013a,b; our unpublished data). Further, these studies have confirmed that over-expression of PHB maintains the mitochondrial transmembrane potential by inhibiting cytochrome c release and activation of caspase-3 (Chowdhury et al, 2007, 2011, 2013). …”
Section: Introductionmentioning
confidence: 68%
“…Our studies have shown that infection of undifferentiated GC from preantral follicles with a PHB adenoviral construct resulted in over-expression of PHB that markedly attenuated ceramide-, staurosporine-, campothecine- and serum withdrawl-induced apoptosis via the intrinsic apoptotic pathway (Chowdhury et al, 2007, 2011, 2013, 2014; Wang et al, 2013a,b; our unpublished data). Further, these studies have confirmed that over-expression of PHB maintains the mitochondrial transmembrane potential by inhibiting cytochrome c release and activation of caspase-3 (Chowdhury et al, 2007, 2011, 2013). …”
Section: Introductionmentioning
confidence: 68%
“…The addition of 100 µM CER to rat lung cells and prostate cancer cells increased BAX, cytochrome C and caspase expressions (Husari et al, 2006). In addition, CER increased apoptosis, cytochrome C and capase-3 levels in cultures of rat granulosa cells (Chowdhury et al, 2011). Therefore, it is likely that CER could be involved in the granulosa cells apoptotic process that results in follicle atresia.…”
Section: Discussionmentioning
confidence: 98%
“…Other anti-apoptotic factors such as PHB contributed to the higher protection against apoptosis provided by Tat101 but not Tat72. PHB is a potent survival factor that inhibits the release of cytochrome c and caspase-3 activation (98,99), and it was increased 70-fold in Jurkat-Tat101, which was 2-fold higher than in Jurkat-Tat72.…”
Section: Discussionmentioning
confidence: 99%